Recepção, mediação e espaço no consumo cinematográfico em Araguaína – TO - Barros, Cristiano Alves (2020)
This work is propose to think about the cinematographic spaces installed in Araguaína-TO, from the spatialities in the places available for film projection and also, the characterization of the visitors in this process of cinematic spectorality. The methdology was based on the research participant method which was used to identify some structural and receptive differentiations in the Mobi Cine and the UFT Cineclub cinema in Araguaína. Interviews were done with the participants after their filmic sessions during the period of August to November of 2017, in order to register their experiences and perceptions during the cinematographic exhibition. From these interviews, the thoretical studies of Bamba (2013), Jacks (2005, 2016), Martín-Barbero (2002, 2009) and other authors who also discuss the cinematographic reception in different contexts of the public and how the mediatic mediations of consumption direct the preferences of the receivers. He sought, therefore, to understand that the filmic access can be differentiated from the experiences that the participant has with the cinematographic medium, from cinemas to virtual platforms that provide a great film collection.